Biodiesel production from Jatropha curcas via two-steps catalyzed process - Sinnathamby, Guganeswaran (2010)
Biodiesel, an alternative renewable fuel made from transesterification of vegetable oil with alcohol, is becoming more readily available for use in blends with conventional diesel fuel for transportation applications. One way of reducing the biodiesel production costs is to use the less expensive feedstock containing fatty acids such as inedible oils, animal fats, waste food oil and by products of the refining vegetables oils. The fact that Jatropha oil cannot be used for nutritional purposes without detoxification makes its use as energy or fuel source very attractive. The effect of main factor which are, temperature, particle size of the meal and reaction time were investigated to optimize the extraction operating conditions for achieving maximum oil yield. The lipid fraction of Jatropha curcas oil seed were extracted and to study the analyzed for their chemical and physical properties such as acid value, percentage free fatty acids (% FFA), iodine value, peroxide value and saponification value as well as viscosity, and density. The fatty acid composition of the extracted lipid was revealed using the (GCMS) method. Biodiesel production process is the transesterification of the used two-steps catalyzed process with jatropha oil and methanol, in the presence of alkali catalyst, to yield the ethyl ester as a product and glycerine as a by-product. In the acid treatment or the acidcatalyzed esterification, the temperature is set at 40°C, acid catalyst of 2%w/wH2SO4. These studies have been performed based on 3 effect, temperature, catalyst concentration and time. As a result, the best condition that has been determined for maximum biodiesel production were 1.5% catalyst concentration of potassium hydroxides based on weight of jatropha curcas oil that were used methanol to jatropha curcas oil of 6:1 and, process were done at temperature 600C and the time is about 60 minutes. Biodiesel yield and moisture content in biodiesel production from jatropha curcas oil were measured. Oil yield content of jatropha kernel was found about 50–60% for different extraction time. Both oleic acid (45.24%) and linoleic acid (31.58%) were detected as the dominant fatty acids while palmitic acid and stearic acid were the saturated fatty acids found in the Jatropha curcas oil. These processes which using ultrasonic reactor is easy and faster than other biodiesel production process because cavities caused by the ultrasound at the catalyst surface increase the catalyst activity and reduce the activation over potential loss.